2017
DOI: 10.5194/acp-2017-991
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temperature (208–318 K) and pressure (18–696 Torr) dependent rate coefficients for the reaction between OH and HNO<sub>3</sub>

Abstract: <p><strong>Abstract.</strong> Rate coefficients (<i>k</i><sub>5</sub>) for the title reaction were obtained using pulsed laser photolytic generation of OH coupled to its detection by laser-induced fluorescence (PLP-LIF). More than eighty determinations of <i>k</i><sub>5</sub> were carried out in nitrogen or air bath gas at various temperatures and pressures. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(23 citation statements)
references
References 24 publications
(41 reference statements)
2
19
1
Order By: Relevance
“…The absorption cross-section for HNO3 at 185 nm, σ185nm, has been determined several times in the literature [15][16][17] . More recently, Dulitz, et al, 10 have confirmed the previous measurements using a meticulous apparatus to account for a variety of impurities (NO2, NO3, N2O5, and H2O) and measure at two wavelengths simultaneously. Based on these studies, σ185nm = (1.6 ± 0.1) × 10 -17 cm 2 was used here.…”
Section: Vuv Absorption -185 Nmmentioning
confidence: 56%
See 4 more Smart Citations
“…The absorption cross-section for HNO3 at 185 nm, σ185nm, has been determined several times in the literature [15][16][17] . More recently, Dulitz, et al, 10 have confirmed the previous measurements using a meticulous apparatus to account for a variety of impurities (NO2, NO3, N2O5, and H2O) and measure at two wavelengths simultaneously. Based on these studies, σ185nm = (1.6 ± 0.1) × 10 -17 cm 2 was used here.…”
Section: Vuv Absorption -185 Nmmentioning
confidence: 56%
“…as a function of temperature and pressure: Margitan and Watson, 8 over the pressure range of 20 -100 Torr and temperature range of 225-415 K, Stachnik, et al, 9 over the pressure range of 10 -730 Torr and at two temperatures of 248 and 297 K, Brown, et al, 5 between 50 and 500 Torr over the temperature range of 200-375 K and the most recent study by Dulitz, et al, 10 over the pressure range of 18 -696 Torr and the temperature range of 208 -318 K. The three earlier studies are in fair agreement which led to the current JPL recommended uncertainty in k1 of 20% (±1σ) at STP.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations